(STUDI KASUS: JORONG PASIE KENAGARIAN TIKU SELATAN KECAMATAN TANJUNG MUTIARA KABUPATEN AGAM) - Zulfayeti, Refina - (Pendidikan Sosiologi, 2014)
This research was motivated presence of poor fishermen house holds in Jorong Pasie because the majority of household head sworking as a fisherman. Income fisherman always erratic and sometimes even a loss making life increasingly difficult for fishermen affected by natural factors. Fishermen whose position as a small fishing classified into different poor fishermen with large fishing in come. Lifeis very poor fishing house holds far from prosperous due to irregular income, making fishermen must do every thing possible to keep it met the needs of clothing, food, housing and childrens education costsare also to be metso tha tthe fishing more difficult.The purposeof this studyis to describe the strategy of the house hold economy of poor fishermen in South survive Jorong Pasie Kenagarian Tiku Selatan. This study uses the theory proposed by James Coleman on rational choice about the actor who is seen as aman of purpose and action focused on efforts to achieve these objectives, the actors them selveshave a choice or value and satisfaction. The research is a qualitative descriptive approach, a technique usedin data collecti on are observation, interview. Selection techniques informant swas purposive sampling(aims) in which the informant set deliberately by the researcher, based on the needs and the adequacy of the amount of research data, the accuracy of the data to be analyzed using techniques Milles and Huberman. The results of this study in dicate that the economic strategy undertaken poor fishing house holds in Jorong Pasie to meet the needs of clothing, food, housing and childrens educationare: doinga side jobin the form of 1) open a coffee shop 2) selfish 3) screaming chicken 4) do the loan. Forms involvement family members ineconomic activity 1) involving wife works for a living and 2) engage the child in making a living.